Competição entre a tiririca (Cyperus rotundus L) e o feijoeiro (Phaseolus vulgaris L) - D William , Raymond (Revista Ceres, 2025)
Competition between dry beans (Phaseolus vulgaris L.) and two nutsedge subspecies (Cyperus rotundus L. and C. rotundus ssp. tuberosus) was studied in Viçosa, Minas Gerais. The two subspecies accounted for 10% and 90% of the nutsedge population, respectively.